RELEVANSI PENERAPAN GOVERNMENT FINANCE STATISTICS (GFS) DALAM MENILAI KEBIJAKAN FISKAL - Puput Waryanto (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2015)
The government need to realize government Finance Statictics (GFS) could be the right choice because a prove that the application of FGS in some countries was relevant to review fiscal policy, by the regression equation Y + 1,810-0,838x where X = application of the GFS and Y =Fiscal policy. It was negative and significant influence, Factor GFS application could asses fiscal policy by contribution of 81.1%. The preparation of the GFS did not terminate the obligation in preparing financial statements for a common purpose, which was at the level of central government known as LKPP (Government Financial Statement). Use of basic principles which were adequate in the GFS, consist of the accrual basis, coverage of public sector, and consolidation also supported this GFS as a basic for decision making on fiscal policy more precisely than a general purpose financial statement. Diffrerences between GFS with government accounting standard (the general government sector), as well as between the GFS with financial accounting standards ( Public enterprise sector), ranging from the purpose, scope, reporting entities, criteria for recognition, measurement. Revaluation and changes is value , and the integration of current and position, were obstacles and challenges for all parties, especially the central government in charge of developing systems, procedures, and resources needed to develop the GFS in Indonesia.